Using data-driven weightings to construct the provincial healthcare system index - Le B-T; Hoang T-H; Ngo T; Pham T-L (Innovative Research Publishing, 2025)
The healthcare system is essential in delivering services that enhance the quality of life and contribute to the Sustainable Development Goals (SDGs) worldwide. Thus, measuring the effectiveness of healthcare systems is important. This study introduces a Provincial Healthcare System Index (PHSI) as a composite index that integrates macro-and micro-level data to assess the readiness and capacity of provincial healthcare systems, with an application to Vietnam, an emerging economy. Importantly, principal component analysis was used to derive data-driven weightings for the PHSI instead of a priori subjectively defined ones. The empirical results show that the average 2021 PHSI in Vietnam is notably low at 0.199, indicating a significant lack of preparation and capacity in converting healthcare resources into outcomes. The marked disparity among neighboring provinces suggests that their healthcare systems are still disconnected. The study highlights the need for Vietnamese policymakers to enhance the resources and outcomes of its provincial healthcare system. Improving provincial connectivity could significantly enhance the overall efficiency of the regional and national healthcare systems in Vietnam. Such implications could be further extended to other emerging economies.
Keywords: Composite indices; Healthcare management; Provincial; Sustainable development goals; Vietnam